Antitumor Activity and Reductive Stress by Platinum(II) N-Heterocyclic Carbenes based on Guanosine** - Leitão, Maria Inês P.S. (2023)
Platinum(II) complexes bearing N-heterocyclic carbenes based guanosine and caffeine have been synthesized by unassisted C−H oxidative addition, leading to the corresponding trans-hydride complexes. Platinum guanosine derivatives bearing triflate as counterion or bromide instead of hydride as co-ligand were also synthesized to facilitate correlation between structure and activity. The hydride compounds show high antiproliferative activity against all cell lines (TC-71, MV-4-11, U-937 and A-172). Methyl Guanosine complex 3, bearing a hydride ligand, is up to 30 times more active than compound 4, with a bromide in the same position. Changing the counterion has no significant effect in antiproliferative activity. Increasing bulkiness at N7, with an isopropyl group (compound 6), allows to maintain the antiproliferative activity while decreasing toxicity for non-cancer cells. Compound 6 leads to an increase in endoplasmic reticulum and autophagy markers on TC71 and MV-4-11 cancer cells, induces reductive stress and increases glutathione levels in cancer cells but not in non-cancer cell line HEK-293.